Brief introduction into information systems & management research in media industries - Lugmayr, Artur (2013)
Within the scope of this paper, a new research field - information systems and management in media industries is introduced. The paper illustrates the importance of viewing the media firm as holistic digital firm from the information systems and management perspective. It reviews current literature, research work, and provides an overview of opened research gaps. © 2013 IEEE.